Tough, Instant, and Repeatable Adhesion of Self‐Healable Elastomers to Diverse Soft and Hard Surfaces - Li, Ke; Zan, Xingjie; Tang, Chen; Liu, Zhuangzhuang; Fan, Jianghuan; Qin, Gang; Yang, Jia; Cui, Wei; Zhu, Lin; Chen, Qiang (Advanced science, 2022)
Repeatability and high adhesion toughness are usually contradictory for common polymer adhesives. Repeatability requires temporary interactions between the adhesive and the substrate, while high adhesion toughness is usually achieved by permanent bonding. Integrating these two features into one adhesive system is still a daunting challenge. Here, the development of a series of viscoelastic elastomers composed of a soft and hard segment is reported, which exhibit tough, instant, yet repeatable adhesion to a variety of soft and hard surfaces. Such a combination of mutually exclusive properties is attributed to the synergy of high mobility of polymer chains and massive viscoelastic dissipation of the elastomers around the interface. By optimizing the relaxation time and mechanical dissipation, the resulting adhesives can achieve a tough yet repeatable adhesion toughness above 2000 J m−2, superior to the best‐in‐class commercial adhesives. Numerous acrylate monomers are proven applicable to the preparation of such adhesives, validating the universality of the fabrication method. The application of these elastomers as adhesive and protective layers in soft electronics by virtue of their universal and tough adhesion to various soft and hard substrates is also demonstrated. Copolymerizing acrylate monomers with contrasting glass transition temperatures of their homopolymers results in an elastomer with a glass transition temperature that is slightly below room temperature. Due to high polymer chain mobility and energy dissipation, the viscoelastic elastomer shows tough, instant, and repeatable adhesion to diverse soft and hard surfaces.